Syn‐Orogenic Exhumation of High‐P Units by Upward Extrusion in an Accretionary Wedge: Insights From the Eastern Elba Nappe Stack (Northern Apennines, Italy). Issue 5 (5th May 2021) - Ryan, E.; Papeschi, S.; Viola, G.; Musumeci, G.; Mazzarini, F.; Torgersen, E.; Sørensen, B. E.; Ganerød, M.
Abstract: The E‐vergent Northern Apennines formed by Oligocene‐Miocene convergence and westward subduction of Adria beneath Europe. Extension ensued in the Mid‐Late Miocene reflecting lower plate roll‐back and causing opening of the back‐arc Northern Tyrrhenian Sea. Post‐orogenic extension is commonly advocated as the main driver of the exhumation of the belt's inner domain high‐pressure/low‐temperature (HP‐LT) rock units. The Acquadolce Subunit of the Eastern Elba nappe stack contains HP‐LT rocks recording peak blueschist conditions of 1.5–1.8 GPa at 320°C–370°C loosely dated to the Oligocene‐Early Miocene. It is sandwiched by two Late Miocene, out‐of‐sequence top‐to‐the E thrusts between Jurassic LP serpentinites on top and HT–LP contact metamorphosed marbles at its base. We document widespread W‐verging ductile asymmetries within the Acquadolce Subunit, which correspond to top‐to‐the W extensional shearing for the nappe stack current orientation. This allowed for early syn‐orogenic exhumation from blueschist‐ to greenschist‐facies conditions, wherein coeval W‐directed extension at the top of the exhuming units acted synchronously with E‐directed thrusting at their base causing exhumation by extrusion in an overall contractional setting. The basal, E‐vergent thrusting is, however, challenging to document as the wedge has since been reworked by Late Miocene, E‐verging compressive tectonics, contact metamorphism, and later extension, obliterating much of the evidence supporting exhumation by extrusion during the early stages of wedge build‐up. Syn‐orogenic exhumation by extrusion from deep structural levels within the orogenic wedge is a viable mechanism to account for other exhumed HP‐LT units in the inner part of the belt. Key Points: Syn‐orogenic extrusion is proposed as a viable mechanism for the exhumation of HP‐LT rock units of the Northern Apennines; The Acquadolce Subunit of the Eastern Elba nappe stack was exhumed by upward extrusion within an actively shortening orogenic wedge; Middle Miocene extension shaped the upper Northern Apennines orogenic wedge but did not contribute to the early exhumation of HP rocks.